Correlation of Angiotensin Converting Enzyme (ACE) Gene Polymorphism and Random Blood Sugar Levels In Obese - Amelia Eka Damayanty; Isra Thristy; Nanda Sari Nuralita (UMSU, 2025)
Background: Obesity is a condition where there is excessive accumulation of fat that can pose a risk to health in the form of the risk of chronic diseases such as type 2 diabetes mellitus (DM). Current blood sugar levels are one of the diagnoses of type 2 DM (T2DM) which is a standard test that describes blood glucose homeostasis. Angiotensin Converting Enzyme (ACE) is an important enzyme in the renin-angiotensin system (RAS) because it catalyzes the conversion of angiotensin I to angiotensin II (Ang II). The RAS component of adipose tissue provides a potential pathway by which obesity can lead to insulin resistance where ACE gene polymorphisms can raise blood sugar levels. Objectives: To analyse the relationship of ACE gene polymorphism with random blood sugar levels as a predictor of type 2 DM risk in obesity. Materials and Methods: The design of this study was observational analytic with a cross-sectional approach. The sample in this study were blood from 35 obesity people in Universitas Muhammadiyah Sumatera Utara and then carried out PCR examination to identify ACE gene polymorphisms and random blood sugar levels. The data were analyzed with the Kruskal Wallis Test. Results: The major samples were in 26-35 years old (42,86%). The most types of ACE gene polymorphisms were type II 51,4%, followed by the type of ID polymorphisms (32,4%), and the least was the type of DD polymorphisms (10,8%). The random blood sugar levels was normal level 80-140mg/dl (74,29%). The Kruskal Wallis test of ACE gene polymorphism and blood sugar levels with p = 0.119 (p 0.05). Conclusion: There was no correlation of ACE gene polymorphism with random blood sugar levels in obesity.